PENGGUNAAN BAHASA INDONESIA DI INDUSTRI PARIWISATA: STUDI KASUS PERENCANAAN BAHASA PADA INDUSTRI PARIWISATA BALI - I Gusti Putu Sutarma; I Ketut Sadia (Politeknik Negeri Bali, 2013)
The phenomenon of the use of Indonesian language in the tourism industry is very appealing for consideration. This is due to the use of Indonesian in the tourism industry in terms of Indonesian planning process has not been running optimally. This is evidenced that the use of a foreign language is more dominant than the Indonesian language. Thus, the aim of this study is to analyze and describe the use of Indonesian in the tourism industry in terms of language planning process. This research is descriptive qualitative and using primary data obtained directly from the data source in the industry that is the use of Indonesian in tourism industry in Nusa Dua, Kuta and Sanur. Data were collected by using observation method assisted with note taking technique. Furthermore, the data were analyzed with descriptive qualitative inductive paradigm; that is the paradigm from specific or particular to general one. The results are presented by using formal and informal methods. As the foundation of this research Sociolinguistics Applied Theory is used with the basic concepts of the language planning process. Based on the results obtained, the use of Indonesian in the tourism industry in terms of Indonesian planning process has not been running optimally. This is proven with the still dominant use of a foreign language than Indonesian in the tourism industry. Based on the language planning process, the stages that have not run well are those of implementation and assessment or evaluation.